PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE MOOD, UNDERSTAND, RECALL, DETECT, ELABORATE, REVIEW (MURDER) UNTUK MENINGKATKAN PRESTASI BELAJAR SISWA PADA POKOK BAHASAN HIDROKARBON DI KELAS X SMA NEGERI 14 PEKANBARU - Siti Istiqomah; Betty Holiwarni; Abdullah ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The porposes of research were to know improvement of student achievement and the effect of the application of cooperative learning model MURDER to increased student achievement on the subject of hydrocarbon in Class X SMAN 14 Pekanbaru. This research was a form of experimental research with the design randomized control group pretest-posttest. The study population was all students of class X at SMAN 14 Pekanbaru. The samples were students of class X.3 as experimental class and class X.2 as the control class. The experimental class was applied cooperative learning model MURDER, while the control class using discussion method. Data were analyzed using t-test. Results from the study showed tcount>ttable (4,58 >1.67) and category increase student achievement in the experimental class at 0,79 with high katergori while the experimental class category increase student achievement by 0.55 with category so it can be concluded the implementation of cooperative learning model MURDER can improve the student achievement on the subject of Hydrocarbon in class X SMAN 14 Pekanbaru.Key Words: Cooperative Learning Model MURDER, Student Achievement, Hydrocarbon